Students’ Attitude towards Online Education System: A Comparative Study between Public and Private Universities in Bangladesh - Khadiza Benta Nasir; Meher Neger (Goodwood Publishing, 2022)
Purpose: This study aimed to inquire about the students’ attitude towards the online education system as well as a comparison has been made between public and private university students’ attitudes. Methodology: The descriptive research methodology was used for this study. Data was collected from 240 students where 120 were public university students and 120 were private university students. A structured and close-ended questionnaire with a seven points scale had been used to collect data. The sampling method was non-probability. Descriptive statistics analysis, reliability analysis, and multiple regression analysis were measured by SPSS 25.0 version. Results: The result shows that the public university students’ attitude has a positive relation to interaction, internet self-efficacy, and students’ self-determination, but has no relationship with course design and technical support. The private university students’ attitude is influenced by all factors except technical support. Conclusions: Online education in Bangladesh allowed students to continue learning during the pandemic. Success depends on teacher-student interaction, student motivation, and a suitable curriculum, enabling timely semester completion in both public and private universities. Limitations: This study focused only on the Bangladeshi students. Contributions: This paper will assist the authority to understand the students’ attitude towards the online education system and take initiatives to make it more acceptable to the students.